Уніфікація судової практики у загальному праві: теоретико-прикладні питання - Головатий, В.; Holovatyi, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена загальнотеоретичному дослідженню питань уніфікації, що здійснюється вищими судовими інстанціями в англо-американському типі правових систем, виявленню її особливостей. Констатується важливість категорії уніфікації судової практики для загального права оскільки вона дозволяє виявити значимість та спрямованість однотипної практики на досягнення такої мети як ефективність правосуддя, відмежувати її від нормативно-правової уніфікації.The article is devoted to the study of general theoretical issues of unification undertaken by the highest court institutions in the Anglo-American type of legal systems and identification of its peculiarities. Analysis of the higher courts practice in Anglo-American (common) type of legal systems allows to conclude, that the unification of judiciary practice is carried out by them in the course of considering the cases and adoption of judicial decisions. This approach to unification results in the convincing and influential judicial precedents. Generalization as a unification strategy is not applied in the judiciary practice of the Anglo-American (common) type of legal systems. The emphasis is laid on the importance of judiciary practice not only for the continental but for the common law too, since it allows to identify the value and the direction of unification practice aimed at the achievement of such goals as the efficiency of justice, determining its differences from normative legal harmonization. Judiciary practice provides further opportunities for identifying appropriate technical and technological requirements for the unification of it in the common law system.
Unification of Judiciary Practice in the Common Law: Theoretical and Applied Issues.
Keywords: англо-американський тип правової системи; судова система Англії; судова система США; судовий прецедент; уніфікація судової практики; Anglo-American type of legal system; the judicial system of England; the US judicial system; unification of judiciary practice; legal precedent